• Предмет: Математика
  • Автор: Аноним
  • Вопрос задан 1 год назад

решите пожалуйста ​пжпжпжжп

Приложения:

Ответы

Ответ дал: Stolas
1

(7 \frac{5}{6}  - 3 \frac{4}{12} )x =  \frac{4}{9}  \\ ( \frac{47}{6}  -  \frac{40}{12} )x =  \frac{4}{9}  \\  \frac{9}{2} x =  \frac{4}{9}  \\ x =  \frac{8}{81}

(9 \frac{1}{3}  + 2 \frac{6}{7} )x =  \frac{6}{7}  \\ ((9 + 2) + ( \frac{1}{3}  +  \frac{6}{7} ))x =  \frac{6}{7}  \\ (11 +  \frac{25}{21} )x =  \frac{6}{7}  \\ (11 + 1 \frac{4}{21} )x =  \frac{6}{7}  \\ 12 \frac{4}{21} x =  \frac{6}{7}  \\  \frac{256}{21} x =  \frac{6}{7}  \\ x =  \frac{9}{128}

Похожие вопросы